Studies on wall pressure of sonic flow through the converging nozzles for different area ratios - Ashfaq, Syed; Khan, Sher Afghan (RS Publication, 2014)
The experimental studies were conducted to ascertain the effectiveness of micro jets to control the base pressure in suddenly expanded axi-symmetric ducts. However, in this paper our main aim was to study the influence of the micro jets on the development of the flow field in the duct wall as well as the control effectiveness of the micro jets. As it is well known that whenever, control is used it is mandatory on the part of the researcher to make sure that the control whether; active or passive control, the control does not disturb or made oscillatory the flow field in the enlarged duct.To achieve this an active control in the form of four micro jets of 1 mm orifice diameter located at 900 intervals along a pitch circle diameter of 1.3 times the nozzle exit diameter in the base region was employed. A convergent nozzle was used and the Mach number at the nozzleexit was unity. The area ratio (ratio of area of suddenly expanded duct to nozzle exit area) studied are 2.56, 3.24, 4.84 and 6.25. The length-to-diameter (i.e. L/D) ratio of the sudden expansion duct was varied from 10 to 1. From the experimental results, it is found that the micro jets can be used as an active controller for base pressure and wall pressure flow field.Further, from the results it is found that the flow field in the suddenly expanded duct is identical for with and without control cases and to quantify the effect of micro jets on the quality of flow in the duct wall pressure was measured and it is found that the micro jets do not disturb the flow field.